(untitled) (Jurnal Manajemen Bisnis, 2024)
Saung Angklung Udjo (SAU) employs various strategies to preserve angklung art and attract domestic tourists. This research explores SAU’s methods, including adapting to consumer behavior, developing new business models, promoting via social media, collaborating with diverse parties, and providing scholarships. SAU innovates with educational programs and music therapy, enhancing engagement through digital promotions and expanding cultural reach through partnerships. Dynamic performance adaptations and involving children are key in attracting audiences and ensuring cultural preservation. Consequently, SAU successfully preserves angklung art while introducing cultural values to the younger generation and broader community through sustainable business strategies.